Factors that influence the acceptance of future shared automated vehicles – A focus group study with United Kingdom drivers. (October 2021) - Dichabeng, Patrick; Merat, Natasha; Markkula, Gustav
Highlights: Acceptance of shared automated vehicles was investigated among United Kingdom private car owners through a focus group. From a long list of factors based on previous research, three main factors (Service Quality, Trust, Price Value) came out as overwhelmingly discussed. Shared Space Quality, Security and Trusting Co-passengers are introduced as important indicators to accept shared automated vehicles. Trusting Co-passengers was found to be as important as Trusting Automated Vehicles. An extended UTAUT2 is proposed for future acceptance research on shared automated vehicles. Abstract: The development of Shared Automated Vehicles (SAVs) is well underway to provide mobility as a service (MaaS) and bring benefits such as reduced traffic congestion, reduced reliance on privately owned vehicles and increased independence to non-drivers. To realise the benefits of SAVs, adoption by private vehicle users is crucial. Previous research has shown this subset of users as the least likely to adopt SAVs, and it is not well understood what factors are important to achieve such adoption. The purpose of this study is to obtain an in-depth understanding of attitudes, perceptions and preferences that influence the acceptance of future SAVs for drivers. This paper presents the results from an online asynchronous focus group study with 21 British drivers as participants. From the analysis, Service Quality, Trust and Price Value emerged as the three most prominent factors to understand user acceptance of SAVs. These three main factors may be of prime importance for convincing naïve private car owners to accept high-speed SAVs. Productive use of travel time has been frequently mentioned in previous research as a benefit of vehicle automation but was scarcely mentioned by participants in this study. Shared Space Quality in introduced as an indicator for Service Quality, together with Security and Trusting Co-passengers as two indicators of Trust. Based on the findings, this paper concludes with a conceptual SAV technology acceptance model is introduced, with the results added as extended model predictors to the Unified Theory of Acceptance and Use of Technology (UTAUT2).